A longitudinal experimental study on the Development of interpersonal relationships in Computer-mediated communication - Mustafa, Hasrina (2004)
The wide-spread use of computer-mediated communication (CMC) in society today has provided new opportunities for the development of relationships. Hence, the need to understand the developmental aspects of relationships in an online setting has become increasingly important, particularly those that concern the effects of time, channel synchrony and relationship types on the development of interpersonal relationships in CMC. The present study used a longitudinal experimental design in order to achieve the objectives of the study. A total of 110 participants were involved in the experiment and they were randomly assigned to face-to-face control group and two treatment groups (synchronous CMC and asynchronous CMC groups). Within each group, participants were assigned to zero-history dyads. Participants in the control group interacted face-to-face, while participants in the synchronous CMC group communicated with their partners using electronic chatting program. Participants in the asynchronous CMC group interacted via electronic mail. All participants attended four experimental sessions conducted once a week over a four weeks' duration. Statistical analyses used in the study were the ANOVA, the Repeated-Measures ANOVA, the Paired Samples t-test and the Independent Samples t-test. The results showed that time was a significant factor for the development of relationships in CMC. The development of relationships in both CMC channels (synchronous CMC and asynchronous CMC) was significantly greater at the later time than at the initial time. However, time was not a significant factor for the development of interpersonal relationships in face-to-face control group. The finding exhibited that channel synchrony was a significant factor for the development of interpersonal relationships in CMC. The development of relationships in both synchronous channels namely face-to-face and synchronous CMC was significantly greater than that in asynchronous CMC. The result also revealed that relationship type was not a significant factor for relational development in CMC. Both relationship types (same-sex and crosssex) in CMC groups showed no difference in the relational progressions. However, relationship type was a significant factor for the development of relationships in face-to-face group, in which same-sex partners showed significantly more developed relationships as compared to cross-sex partners. The study concludes that interpersonal relationships do occur over time in CMC, despite obvious channel limitations as compared to face-to-face communication.